Effects of Metformin on Menstrual Cyclicity in Women with Polycystic Ovary Syndrome - Bayar, Ülkü; Mungan, Görkem; Başaran, Mustafa; Kıran, Sibel; Akbulut, Volkan; Can, Murat (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To evaluate eff ects of metformin on menstrual cyclicity in women with polycystic ovary syndrome. STUDY DESIGN: The study was designed as pre-, post prospective clinical trial. To enter the study, patients had to have well-documented PCOS, be oligo-(six cycles or less in the preceding year) or amenorrheic (absence of menstrual cycles for 1 year), and not have exclusionary diseases or drugs. Metformin 500 mg orally twice daily was administered for 6 months. Serum fasting insulin, glucose, FSH, LH, estradiol, progesterone, prolactin, free testosterone, DHEAS, total cholesterol, triglyceride, AST, ALT, HDL, LDL, VLDL were measured. Quantitative insulin sensitivity check index (QUICKI) was used to measure the insulin resistance. Blood samples were collected at the initiation of therapy and 6 months after. Follow-up 6 months was scheduled with interval history, review of menstrual status, assessment of any metformin-related side effects, brief physical and laboratory examination. RESULTS: Total 13/23(39.1%) of the patients with metformin treatment resumed normal menses 6 months after. Nine of 19 oligomenoreic women (47.4%) resumed regular normal menses; 4 of 4 (100%) amenoreic women resumed oligomenoric menses. The fasting blood glucose, fasting blood insulin, free testesteron, VLDL levels were decreased after 6 months of treatment (p=0.005; p= 0.002; p= 0.008; p=0.006 respectively ). First and sixth months measurements of QUICKI were found significantly different (p=0.000). CONCLUSION: Metformin therapy is well tolerated by the majority of patients and may be clinically useful, in nonobese patients with PCOS and menstrual disturbances.